2017
DOI: 10.1158/2326-6066.cir-16-0195
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Tumor DNA Repair Expression and T-cell Infiltration in Breast Cancers

Abstract: Impaired DNA repair drives mutagenicity, which increases neoantigen load and immunogenicity. We investigated the expression of proteins involved in the DNA damage response (ATM, Chk2), double-strand break repair (BRCA1, BLM, WRN, RECQL4, RECQL5, TOPO2A, DNA-PKcs, Ku70/Ku80), nucleotide excision repair (ERCC1), base excision repair (XRCC1, pol β, FEN1, PARP1), and immune responses (CD8, PD-1, PD-L1, FOXP3) in 1269 breast cancers and validated our findings in an independent estrogen receptor (ER) -cohort (n = 27… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 23 publications
2
54
1
Order By: Relevance
“…Tumors that expressed low XRCC1 were associated with high CD8 þ tumor-infiltrating lymphocyte (TIL) counts, aggressive phenotype and reduced survival. Importantly, PD-1 þ or PD-L1 þ breast cancers with low XRCC1 were linked to aggressive cancers and reduced survival including in ERbreast cancers (13). As immune microenvironment (including PD-L1 þ TILs infiltration) in DCIS can influence aggressive phenotypes (28,29), we propose that PARP1 targeting may be a promising personalized approach either alone or in combination with immune checkpoint inhibitors in XRCC1deficient invasive cancers and in preinvasive DCIS.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Tumors that expressed low XRCC1 were associated with high CD8 þ tumor-infiltrating lymphocyte (TIL) counts, aggressive phenotype and reduced survival. Importantly, PD-1 þ or PD-L1 þ breast cancers with low XRCC1 were linked to aggressive cancers and reduced survival including in ERbreast cancers (13). As immune microenvironment (including PD-L1 þ TILs infiltration) in DCIS can influence aggressive phenotypes (28,29), we propose that PARP1 targeting may be a promising personalized approach either alone or in combination with immune checkpoint inhibitors in XRCC1deficient invasive cancers and in preinvasive DCIS.…”
Section: Discussionmentioning
confidence: 95%
“…However, biomarkers that could predict such an approach are currently unknown. We recently investigated XRCC1 and T-cell infiltration in invasive breast cancers (13). Tumors that expressed low XRCC1 were associated with high CD8 þ tumor-infiltrating lymphocyte (TIL) counts, aggressive phenotype and reduced survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BRCA1 deficiency results in genomic instability and individual's susceptibility to breast and ovarian cancer [20][21][22]. Recently, Green and colleagues reported that low BRCA1 expression was associated with high numbers of CD8 + TILs and poor survival in patients with breast cancer [23].…”
Section: Introductionmentioning
confidence: 99%